Effect of Water Contamination on the Transition Metal Dissolution in Water-Enriched Electrolyte: A Mechanistic Insight into a New Type of Dissolution - Lüchtefeld, Janik; Hemmelmann, Hendrik; Wachs, Susanne; Mayrhofer, Karl; Elm, Matthias T.; Berkes, Balazs B. (Journal of Physical Chemistry C, 2022)
Transition metal (TM) dissolution from cathode active materials is a major factor in accelerating Li-ion battery aging. Residual moisture in the battery is suspected to enhance this degradation mechanism by reacting with the electrolyte, generating acidic species and other decomposition products. In previous studies, we presented a method to track the dissolution in real-time. In the present study, we demonstrate with this method the effect of water on the dissolution of TMs from LiNi0.33Co0.33Mn0.33O2 (NCM111) and LiCoO2 (LCO) used as thin-film model cathodes. We show highly increased dissolution rates in electrolytes with 100 and 1000 ppm of water added and a concomitant decline in electrode performance. More interestingly, we observe a novel hitherto undisclosed dissolution phenomenon during the cathodic back scan and with that give insight into a new dissolution mechanism. This study further reveals that the impact of moisture on TM dissolution may be mitigated by replacing the standard conductive salt, LiPF6, with hydrolysis-stable LiC2NO4F6S2 (LiTFSI).
CRIS-Team Scopus Importer:2022-10-21